Gaussian basis sets to the theoretical study of the electronic structure of perovskite (LaMnO3) - Treu, O.; Pinheiro, J. C.; Kondo, R. T.; Marques, RFC; Paiva-Santos, C. O.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. (Elsevier B.V., 2003)
The Generator Coordinate Hartree-Fock (GCHF) method is applied to generate extended (20s14p), (30s19p13d), and (31s23p18d) Gaussian basis sets for the 0, Mn, and La atoms, respectively. The role of the weight functions (WFs) in the assessment of the numerical integration range of the GCHF equations is shown. These basis sets are then contracted to [5s3p] and [11s6p6d] for 0 and Mn atoms, respectively, and [17s11p7d] for La atom by a standard procedure. For quality evaluation of contracted basis sets in molecular calculations, we have accomplished calculations of total and orbital energies in the Hartree-Fock-Roothaan (HFR) method for (MnO1+)-Mn-5 and (LaO1+)-La-1 fragments. The results obtained with the contracted basis sets are compared with values obtained with the extended basis sets. The addition of one d polarization function in the contracted basis set for 0 atom and its utilization with the contracted basis sets for Mn and La atoms leads to the calculations of dipole moment and total atomic charges of perovskite (LaMnO3). The calculations were performed at the HFR level with the crystal [LaMnO3](2) fragment in space group C-2v the values of dipole moment, total energy, and total atomic charges showed that it is reasonable to believe that LaMnO3 presents behaviour of piezoelectric material. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Gaussian basis sets; Generator Coordinate Hartree-Fock method; perovskite; LaMnO3; piezoelectric